Implikasi Kebijakan Penjualan Microchip Taiwan Dalam Pasar Ekonomi Global: Analisis Poliheuristik - Nugroho Putri, Adinda Ayu Melati; Aprilia Sri Lestari; Nadia Puspita Wijaya; Rafli Alfaizi Hakim (Talenta Publisher, 2024)
In semiconductor-dependent times, Taiwan through its companies was able to lead global semiconductor production. This is due to the Taiwanese government that strongly supports the expansion of its semiconductor industry, especially in the global economic market. This article discusses the factors of the Taiwanese government to advance the semiconductor industry despite Taiwan's economic conditions that previously depended on the agricultural sector through polyheuristic analysis. This research uses a qualitative method with a case study type and data collection using the document study method with grounded theory analysis technique. This research discusses the implications of Taiwan's policies to develop its semiconductor industry in several aspects, such as economic, political, and environmental. The results that the author gets from this polyheuristic analysis are that Taiwan does need to develop its semiconductor industry in the global market because it can help the economy and national security. On the other hand, this policy also provides challenges, especially in the environmental sector. Waste from the semiconductor industry has a major impact on the environment, hence the need for increased semiconductor waste treatment by the Taiwanese government